Enzymatic-Treatment And Different Drying Conditions On Gac Aril (Momordica Cochinchinensis Spreng.) Powder - Sidik, Nur Ain Rafidah Md (Universiti Sains Malaysia, 2020)
Gac (Momordica Cochinchinensis Spreng) is an orange-reddish colour and ovally-shape fruit with spikes that mainly contain higher total carotenoid content. The aim of this study is to investigate the quality of gac aril powder produced upon different drying process. Treatment with pectinase enzyme was done on the fresh gac aril prior to drying treatment. Two type of drying conditions namely hot air drying at temperature 40°C (HA40) and 60°C (HA60), and freeze drying (FD) were carried out to produce gac aril powder. The effect of drying parameter on quality of gac aril powder produced were analyses in term of drying yield, pH, moisture content, water activity, water solubility, water holding capacity, total carotenoids content, and colour. From the results obtained, FD gac aril powder yield significantly lower (p<0.05) amount compared to HA40 and HA60 samples. Moisture content of HA40 and HA60 gac aril powders were significantly lower (p<0.05) compared to FD gac aril powder. However, the result was in contrast in term of water activity. HA40 and HA60 gac aril powders were also significantly higher (p<0.05) in term of water solubility compared to FD sample. Apart from that, FD gac aril powder preserved some components in term of total carotenoid content, water holding capacity, and colour compared to both hot air dried samples. FD gac aril powder give significantly higher (p<0.05) total carotenoid content and significantly lower (p<0.05) total colour different compared to HA40 and HA60. In conclusion, FD samples give the best drying treatment in order to preserve the quality of the gac aril powder produced.